Luteolin attenuates CCl4-induced hepatic injury by inhibiting ferroptosis via SLC7A11 - Zhiqiang Han; Batudeligen; Hongmei Chen; Narisu; Anda; Yanhua Xu; Lan Xue (BMC, 2024)
Abstract Background Luteolin (3,4,5,7-tetrahydroxy flavone) is reported to strongly protect from acute carbon tetrachloride (CCl4) -induced liver injury or fibrosis. Ferroptosis can be induced by hepatic injury, and contributes to liver fibrosis development. The exact functional mechanism underlying luteolin inhibition of hepatic injury and whether ferroptosis is involved are unclear. Methods Mice model and cell model of liver injury were constructed or induced to explore the effect and molecular mechanisms of Luteolin in the treatment of hepatic injury using CCl4. Cell Counting Kit-8 (CCK-8) and flow cytometry were used to evaluate HepG2 cell viability and apoptosis. The differential expressed genes involved in liver injury were scanned using RNA-seq and confirmed using functional study. Western blot was used to detect the indicators related to ferroptosis. Results Luteolin attenuated hepatic injury by alleviating cell morphology and decreasing serum aspartate aminotransferase (AST), alanine aminotransferase (ALT), and alkaline phosphatase (ALP) levels in vivo mice models, and increasing cell viability, downregulating arachidonate 12-lipoxygenase (ALOX12), cyclooxygenase-2 (COX-2) and P21 protein expression, suppressing apoptosis in vitro cell models. Luteolin also inhibited ferroptosis by stimulating glutathione peroxidase 4 (GPX4) and mitochondrial ferritin (FTMT) protein expression, increasing glutathione (GSH) content, and minimizing Fe2+ and malondialdehyde (MDA) levels. Solute carrier family 7a member 11 (SLC7A11) was identified to be a key regulatory gene that participated in luteolin attenuation of CCl4-induced hepatic injuries in HepG2 cells using Microarray assay. Functional study showed that SLC7A11 can alleviate hepatic injury and ferroptosis. Conclusion Luteolin attenuated CCl4-induced hepatic injury by inhibiting ferroptosis via SLC7A11. SLC7A11 may serve as a novel alternative therapeutic target for hepatic injury.